PATRIMÔNIO ARQUITETÔNICO: os desafios para a preservação do Centro Histórico de São Luís. - SILVA, João Ricardo Costa (2016)
This thesis aims to analyze through a sociology of patrimonial practices actions and policies effected by heritage management agencies specifically IPHAN (Union), DPHAP-MA (State), the FUMPH (Municipality), administrative agencies responsible for preservation of architectural heritage, developed in the historic center of São Luís. For situate the study theme was made an explanation about the history of reflections on the preservation of historical heritage and historical aspects of formation of urban space. To measure the performance of actions to preserve the heritage a series of graphs was developed with sociodemographic information from more than three decades. They were created by the classification of population and household variables area with data from the IBGE. The research is a reflection as the successive stages of interventions have managed to preserve a considerable part of the urban complex of Portuguese type, but it is also possible to infer the existence of several problems for the full protection of historical heritage of São Luís. It is concluded that despite the great emphasis the inclusion on the List of World Heritage, the differing challenges for reuse of architectural heritage are still a major obstacle to their preservation.